EVALUASI PROGRAM AKPMM (ALIH KREDIT PENGAKUAN MASA MENGAJAR) DALAM PENINGKATAN KUALITAS PENDIDIKAN JARAK JAUHDI UNIVERSITAS TERBUKA - Kristanti, Dwi; Asnamawati, Lina (Jurnal PGSD, 2016)
This study aimed to evaluate the program AKPMM (Alih Kredit Pengakuan Masa Mengajar, Credit Transfer Recognition Teaching Period) in improving the quality of long distance education in UPBJJ UT (ADivision of Long Distance Learning Program in the Open University). AKPMM program was evaluated from the dimensions of implementation, effectiveness, and program performance. The location of this research is in the UPBJJ UT Padang and Bengkulu. The sample in this study amounted to 210 students. Simple linear regression was used to test the relationship between the variables in this study. The results of this study indicate that the AKPPM program can be implemented better in UPBJJ UT Padang compared UPBJJ UT Bengkulu. In terms of ratios, the number of students who take the program AKPMM in the UPBJJ-UT Bengkulu larger than UPBJJ UT Padang. In terms of program evaluation, it was found that the program AKPMM more positively impact on the students in UPBJJ-UT Padang compared with the students in the UPBJJ-UT Bengkulu. Thisstudy also found that a significant difference among the implementation, evaluation, and effectiveness variables of AKPMM program in the Open University.